Factores Estresores y Estrategias de Afrontamiento Utilizadas por los Docentes. - Sierra Osorio, Zuly Marcela (Universidad Antonio Nariño, 2021)
The general objective of this study was to establish the stressors and the coping strategies used by the teachers of basic primary and basic secondary education of the Liceo Quindío Salento Educational Institution, using a descriptive quantitative methodology. The sample consisted of 25 teachers of which 10 correspond to basic primary and 15 to basic secondary; the information was obtained through the application of the instruments Scale of sources of stress in teachers (E.F.E.P) and the Inventory of Coping Strategies (CSI). The results indicated that in terms of stressors in the case of elementary school teachers, supervision by the hierarchical structure is the most representative stress factor; On the other hand, in the teachers of basic secondary it is evidenced as the most representative stressor factor: the assessment of work by others, in terms of coping strategies it was possible to show that the two population groups (basic primary and basic secondary) The most widely used strategies were problem solving and cognitive restructuring, it was concluded that teachers are significantly affected by the perceptions of overflowing situations and that they are more oriented to the use of problemdirected coping strategies.